Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/rse2.170
|View full text |Cite
|
Sign up to set email alerts
|

Classifying wetland‐related land cover types and habitats using fine‐scale lidar metrics derived from country‐wide Airborne Laser Scanning

Abstract: Mapping 3D vegetation structure in wetlands is important for conservation and monitoring. Openly accessible country‐wide Airborne Laser Scanning (ALS) data—using light detection and ranging (lidar) technology—are increasingly becoming available and allow us to quantify 3D vegetation structures at fine resolution and across broad spatial extents. Here, we develop a new, open‐source workflow for classifying wetland‐related land cover types and habitats using fine‐scale lidar metrics derived from country‐wide ALS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…As most LiDAR studies have focussed on forests and woody habitats (Bakx et al., 2019; Davies & Asner, 2014), it remains open to what extent LiDAR can capture vegetation structure of low‐stature habitats such as grasslands, dunes and wetlands. Some previous studies show promising results for measuring 3D vegetation structure in grasslands and wetlands (e.g., Alexander et al., 2015; Koma et al., 2020; Zlinszky et al., 2014). However, country‐wide LiDAR surveys are often conducted in the leaf‐off season to optimize terrain mapping (Reutebuch et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As most LiDAR studies have focussed on forests and woody habitats (Bakx et al., 2019; Davies & Asner, 2014), it remains open to what extent LiDAR can capture vegetation structure of low‐stature habitats such as grasslands, dunes and wetlands. Some previous studies show promising results for measuring 3D vegetation structure in grasslands and wetlands (e.g., Alexander et al., 2015; Koma et al., 2020; Zlinszky et al., 2014). However, country‐wide LiDAR surveys are often conducted in the leaf‐off season to optimize terrain mapping (Reutebuch et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…into metrics which statistically aggregate the 3D point cloud information within raster cells (Davies and Asner 2014, Bakx et al 2019). LiDAR metrics can then be used to map animal habitats (Lucas et al 2019, Koma et al 2020) or to model the geographical distribution of animals such as birds, mammals and invertebrates (Zellweger et al 2013, 2014, Bakx et al 2019). Most applications have shown that the distribution and abundance of birds and other taxa are related to the vertical and horizontal heterogeneity of the vegetation as measured by various LiDAR metrics (Davies and Asner 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that ALS has also the potential to be used in non‐forested habitats such as wetlands, e.g. for quantifying vegetation height (Hladik and Alber 2012, Luo et al 2015, Nie et al 2018), for mapping the density and biomass of reed beds (Corti Meneses et al 2017, Luo et al 2017), or for classifying wetland‐related habitat types (Koma et al 2020). This is remarkable because wetland habitats such as marshes, reedbeds, swamps or peatlands predominantly consist of low vegetation which limits the detection of vegetation structure with LiDAR.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a high proportion of swamp derived from the land cover map (landcover_propswamp) indicated a low probability of occurrence of that species because it tends to avoid swamp vegetation for breeding (Cramp, 1992). The vegetation cover metric derived from LiDAR (lidar_C_ppr) indicates the density of reed, where the Savi's warbler prefers more open reed vegetation such as land reed (Koma, Seijmonsbergen, et al, 2021). Overall, the results of the Savi's warbler encourage the synergetic use of different RS products for modelling the habitat suitability of wetland birds.…”
Section: Discussionmentioning
confidence: 99%
“…Close to the water edge, reed vegetation (water reed) grows taller and thicker than in reedbeds that are located in the drier parts of a wetland (i.e. land reed) (Graveland, 1998; Koma, Seijmonsbergen, et al, 2021).…”
Section: Methodsmentioning
confidence: 99%